2019
DOI: 10.1186/s12941-019-0318-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal antibiotics with measures of infant adiposity and the gut microbiome

Abstract: Background Prenatal antibiotic exposure has been associated with an altered infant gut microbiome composition and higher risk of childhood obesity, but no studies have examined if prenatal antibiotics simultaneously alter the gut microbiome and adiposity in infants. Method In this prospective study (Nurture: recruitment 2013–2015 in North Carolina, United States), we examined in 454 infants the association of prenatal antibiotic exposure (by any prenatal antibiotic expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 20 publications
5
55
0
Order By: Relevance
“…One is that maternal microbiome changes induced through antibiotic use lead to neonatal acquisition of a more disordered, higher risk microbiome. 20 Our observation that maternal antibiotic use is associated with a moderate frequency of otitis media that decreases with time is consistent with a disordered infant microbiome that is gradually restored. Second, there may be direct anatomic or structural impacts from foetal middle ear antibiotic exposures that might not be reversible and lead to consistently high rates of otitis media.…”
Section: Discussionsupporting
confidence: 73%
“…One is that maternal microbiome changes induced through antibiotic use lead to neonatal acquisition of a more disordered, higher risk microbiome. 20 Our observation that maternal antibiotic use is associated with a moderate frequency of otitis media that decreases with time is consistent with a disordered infant microbiome that is gradually restored. Second, there may be direct anatomic or structural impacts from foetal middle ear antibiotic exposures that might not be reversible and lead to consistently high rates of otitis media.…”
Section: Discussionsupporting
confidence: 73%
“…Across an number of studies, a consistent association has been found between antibiotic-induced changes in the gut microbiota and either childhood adiposity or obesity [ 121 , 122 , 123 , 124 , 125 ]. Zhang and colleagues investigated the influence that prenatal antibiotic exposure had on infant weight for length score (WFL-score), adiposity, and alterations in the gut microbiota [ 121 ]. A total of 237 of the 454 infants included in the study were exposed to antibiotics during gestation, which, for the purposes of the study, was defined as second-trimester exposure.…”
Section: Human Studies Linking Early-life Antibiotic Exposure To Omentioning
confidence: 99%
“…The effect on both mother’s and child’s health of administering antibiotics during pregnancy or around the time of birth has not been completely elucidated. Several studies have been carried out to investigate the potential adverse effects of using antibiotics prenatally, during pregnancy or neonatally on the baby’s gut microbiome and the development of the infant immune system—possibly leading to childhood atopy, asthma, allergy and obesity [ 67 , 68 ].…”
Section: Gut Microbiota At Birthmentioning
confidence: 99%